2013
DOI: 10.1007/s13201-013-0097-y
|View full text |Cite
|
Sign up to set email alerts
|

Geophysical borehole logging for control of driller’s records: hydrogeological case study from Voltaian sedimentary rocks in northern Ghana

Abstract: The low borehole yielding potential and the high drilling failure rate of the Voltaian sedimentary rocks of Northern Ghana have been of concern to many local hydrogeologists and international donors. Consequently, several donor-supported projects have been instituted within the last few years with the view to study the hydrogeological characteristics of this 'difficult' rock system. One such project is the geophysical borehole logging of 13 boreholes drilled into the Voltaian sedimentary rocks of Northern Ghan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Regions having greater yields (more than 3060 Lpm) are limited. Comparison with other sedimentary basins in Africa showed that mean borehole yield in the Sokoto basin was greater than values obtained from the Voltaian sedimentary aquifers in Northern Ghana (0.3 to 72 5-1200 Lpm) [88]. In Ghana's alluvial province, the estimated borehole yield ranged from 1 to 15 m 3 /h [89].…”
Section: Hydrogeological Conditions Of Sokoto Basin Compared To Other...mentioning
confidence: 78%
“…Regions having greater yields (more than 3060 Lpm) are limited. Comparison with other sedimentary basins in Africa showed that mean borehole yield in the Sokoto basin was greater than values obtained from the Voltaian sedimentary aquifers in Northern Ghana (0.3 to 72 5-1200 Lpm) [88]. In Ghana's alluvial province, the estimated borehole yield ranged from 1 to 15 m 3 /h [89].…”
Section: Hydrogeological Conditions Of Sokoto Basin Compared To Other...mentioning
confidence: 78%
“…in hard rocks (Telford et al 1990). These borehole logging tools offer one of the most reliable ways of detecting fractured sections intercepted by the borehole, since some of these fractures may be masked and detected as a single anomaly during a surface geophysical measurements (Agyekum 2009;Awini 2009;Ratnakar and Singh 2008;Krishnamurthy et al 2003;Lee et al 1991;Lee 1985). Gamma log is an important and standard nuclear radiation logging tool, which can be operated in both cased and opened boreholes filled with air, water or drilling fluid, giving them an advantage over electrical logging suites (Kearey et al 2002;Driscoll 1986).…”
Section: Introductionmentioning
confidence: 99%
“…It is generally used as one of the primary tool for lithological investigation (Keys 1997). For instance in Ghana, Agyekum et al (2013) deployed the natural gamma detectors embedded in the five exploratory logging tools to investigate significant discrepancies between the logging results and the driller's/geologist's logs results on reported drilled depths, construction depths, and screen settings of boreholes in the Voltaian sedimentary rocks.…”
Section: Introductionmentioning
confidence: 99%